The Role of Self Efficacy, Risk Tolerance and Entrepreneurial Education on Entrepreneurial Intention of University Students During Digital Transformation Era - Arijanto, Rudy (International Journal of Social and Management Studies, 2023)
The purpose of this study was to analyze the effect of self-efficacy on student entrepreneurial intention, the effect of risk tolerance on student entrepreneurial intention, the effect of entrepreneurial education on student entrepreneurial intention, the effect of entrepreneurial education on student self-efficacy, the effect of risk tolerance on student self-efficacy. This research method is quantitative. survey, research data were obtained by distributing online questionnaires to 340 students who were determined through simple random sampling, the questionnaire was designed using a Likert scale of 7. Data analysis used structural equation modeling (SEM) with SmartPLS 3.0 software tools. The stages of data analysis are validity, reliability and significance tests. The results of this study indicate that there is a positive and significant influence between self-efficacy on student entrepreneurial intention, there is a positive and significant effect between risk tolerance on student entrepreneurial intention, there is a positive and significant influence between entrepreneurial education on student entrepreneurial intention, there is a positive and significant effect between entrepreneurial education on student self-efficacy, there is a positive and significant effect between risk tolerance on student self-efficacy.